2003
DOI: 10.1007/s00122-003-1323-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow among different taxonomic units: evidence from nuclear and cytoplasmic markers in Cedrus plantation forests

Abstract: Hybridization and introgression are important natural evolutionary processes that can be successfully investigated using molecular markers and open- and controlled-pollinated progeny. In this study, we collected open-pollinated seeds from Cedrus atlantica, Cedrus libani and C. libani x C. atlantica hybrids from three French-plantation forests. We also used pollen from C. libani and Cedrus brevifolia to pollinate C. atlantica trees. The progeny were analyzed using three different types of molecular markers: RAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
0
34
0
2
Order By: Relevance
“…The possibility of hybridization (Fady et al 2003), together with recent results of cytological (Bou DagherKharrat et al 2001), isoenzymatic (Scaltsoyiannes 1999), AFLP (Bou Dagher-Kharrat et al 2007) and cpDNA and mtDNA phylogeny analyses (Qiao et al 2007) pointed out the close genetic relationships among Mediterranean cedar taxa and suggest for them the subspecific taxonomic rank. The studies on genetic diversity and phylogeography of C. atlantica (Terrab et al 2006(Terrab et al , 2008, genetic diversity of C. libani (Semaan and Dodd 2008) and C. brevifolia (Eliades et al 2011) described the high level of genetic variation and significant differences among studied populations of compared species.…”
Section: Introductionmentioning
confidence: 83%
“…The possibility of hybridization (Fady et al 2003), together with recent results of cytological (Bou DagherKharrat et al 2001), isoenzymatic (Scaltsoyiannes 1999), AFLP (Bou Dagher-Kharrat et al 2007) and cpDNA and mtDNA phylogeny analyses (Qiao et al 2007) pointed out the close genetic relationships among Mediterranean cedar taxa and suggest for them the subspecific taxonomic rank. The studies on genetic diversity and phylogeography of C. atlantica (Terrab et al 2006(Terrab et al , 2008, genetic diversity of C. libani (Semaan and Dodd 2008) and C. brevifolia (Eliades et al 2011) described the high level of genetic variation and significant differences among studied populations of compared species.…”
Section: Introductionmentioning
confidence: 83%
“…Patterns of genetic variation were examined using two DNA marker types with different inheritance modes: biparentally inherited (nuclear microsatellites: Chaib et al 2006) and paternally inherited (chloroplast microsatellites: Fady et al 2003, who found that chloroplast DNA-referred to as ''plastid''-is paternally inherited in this genus). Attempts to detect variation at maternally inherited mitochondrial DNA failed due to lack of polymorphism (Eliades 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies that have estimated the individual selfing rates and ID under natural mating systems, by calculating the proportion of empty seeds and with biparentally inherited molecular markers such as isozymes, which need more complicated statistical estimators (Kärkkäinen and Savolainen, 1993;Ritland and Travis, 2004;Bower and Aitken, 2007). In this study, we took benefit of the high diversity and paternal inheritance of cpSSRs markers in Pinaceae species (Parducci et al, 2001;Ribeiro et al, 2002;Naydenov et al, 2005) and particular Cedrus (Fady et al, 2003;Terrab et al, 2006). In Cedrus, we measured a mean selfing rate circa 0.1, which is in agreement with the absence of incompatibility mechanisms and the values reported in other conifers (Franklin, 1969;Cottrell and White, 1995;Sorensen, 1999;Restoux et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from 50 mg of fresh plant tissue using the Qiagen Extraction kit (Qiagen, Courtaboeuf, France). The PCRs were performed following the protocol by Fady et al (2003). Electrophoresis was conducted in an Li-Cor sequencer.…”
Section: Genetic Markersmentioning
confidence: 99%
See 1 more Smart Citation